Study of initial alkali charge effects on properties of soda beech pulp by regression models - Davod Efhami (Regional Information Center for Science and Technology (RICeST), 2011)
In this work effect of initial alkali charge were investigated on the yield and kappa number of soda beech pulp and alkali consumption pattern. The results indicated that, the regression models are useful for studying the relations between yield, kappa number and alkali consumption. Soda cooking was performed in 30, 40, 50, 60 and 70 gr.lit-1 initial alkali concentration and five different cooking times. The chips dimensions were in the range of 3-5 cm length, 1-2 cm width and 0.05 cm thickness. The results showed that increasing of alkali charge decreased the time of cooking in the same yield or kappa number. Deligninifaction decreased significantly in kappa number lower than 30. In the same kappa number, increased alkali charge gave a lower yield. The alkali consumption was regularly decreased with increasing of initial alkali charge from 30 to 70 gr/lit, but alkali charge consumption pattern varied in less and more than 30 kappa numbers.